Innovation in the Lithuanian economy: The impact of public attitudes in the media on job selection - Rastenienė, Aušra; Giedraitis, Vincentas R. (Publishing House of the Wrocław University of Economics, 2009)
The goal of this article is to present a theoretically grounded understanding of society’s attitude towards business people and civil servants as one of the important factors of competitiveness through innovation. Society’s attitude towards these groups could influence their creativity, the incentives to create their own business, the feeling of common destiny, the interaction between them, and the effectiveness of their work. The hypothesis, which is going to be tested, is “society’s attitude, as measured through the media towards business people and civil servants influences one’s choice of job or career, specifically, whether to work in the public or private sector.” We will examine this hypothesis using content analysis of newspapers over a 5 year period as a way to gauge public attitudes towards certain types of professions. We will also analyze secondary data of the labour force structure and its changes. In the conclusion the results of this analysis are compared and the hypothesis will be either supported or denied. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 389-396